Phenotypic expression of floral traits in hybrid zones provides insights into their genetic architecture. Issue 3 (1st May 2020) - Scopece, Giovanni; Palma‐Silva, Clarisse; Cafasso, Donata; Lexer, Christian; Cozzolino, Salvatore
Summary: Information on the genetic architecture of phenotypic traits is helpful for constructing and testing models of the ecoevolutionary dynamics of natural populations. For plant groups with long life cycles there is a lack of line cross experiments that can unravel the genetic architecture of loci underlying quantitative traits. To fill this gap, we propose the use of variation for phenotypic traits expressed in natural hybrid zones as an alternative approach. We used data from orchid hybrid zones and compared expected and observed patterns of phenotypic trait expression in different early‐generation hybrid classes identified by molecular genetic markers. We found evidence of additivity, dominance, and epistatic interactions for different phenotypic traits. We discuss the potential of this approach along with its limitations and suggest that it may represent a realistic way to gain an initial insight into the heritability and genomic architecture of traits in organismal groups with complex life history, such as orchids and many others.